Barriers and opportunities for innovation in rice production in the inland valleys of Benin - TOTIN, Edmond; van MIERLO, Barbara; SAIDOU, ALIOU; MONGBO, ROCH LAMBERT; AGBOSSOU, KOSSI EULOGE; STROOSNIJDER, Leo; LEEUWIS, Cees (My University, 2012)
This study investigates the technical and institutional factors that hinder the effective use of irrigation water and the development of the local rice value chain in an inland valley of Benin. Primary data have been collected in three areas: Koussin-Lélé, Bamè and Zonmon. The diagnosis indicates that both local and higher level institutional barriers affect the development of the local rice value chain negatively. The barriers to innovation include an unclear division of responsibilities between local farmer groups and the government for canal maintenance, a lack of effective local rules for the distribution and maintenance of the irrigation infrastructure and distrust among farmers, related to privileges of the farmer leaders, as well as the constraining formal and informal credit systems and uncertain market outlets. The barriers depress rice output and the income of farmers. The windows of opportunity to stimulate innovation comprise consumers’ affinity to local products and territorial product labels, private–public community partnerships, the irrigation potential of inland valleys by the use of small pumps in combination with shallow tube well irrigation.
Keywords: Institutions - Water management - Innovation - Rice value chain - Benin